Analysis of the performance of photovoltaic systems in Slovenia. (1st March 2019) - Seme, Sebastijan; Sredenšek, Klemen; Štumberger, Bojan; Hadžiselimović, Miralem
Highlights: An isotropic model for predicting the solar radiation on inclined surface was used. Differences between measured and simulated values of solar radiation were analysed. The performance analyses were carried out for 3326 PV systems in Slovenia. Abstract: The primary objective of this paper is review state of the art photovoltaic systems in Slovenia (European Union) and their performance analysis. The performance analysis was compared with other countries around the world. The performance analysis of photovoltaic systems was performed in different seasons and weather conditions. The performance ratio is the ratio between final yield and reference yield and depends mainly on the intensity of solar radiation and module temperature. As a consequence of the weather and geographical diversity of Slovenia, performance ratio is more appropriate to describe the performance of photovoltaic systems than final yield, which describes the relationship between the energy produced and the maximum peak power of a photovoltaic system. The results in this paper show that the performance of photovoltaic systems primarily depends on the proper inclination and azimuth angle of the photovoltaic modules, shadings, and snow barrier. The analysis of operational data was carried out for 3326 photovoltaic systems, installed between 2005 and 2018 with a total peak power of approximately 258 MW. The mean annual values of the final yield, performance ratio, and capacity utilization factor were 1038 kWh/kWp, 68.84%, and 11.85%, respectively, for photovoltaic systems in Slovenia.